2017
DOI: 10.1103/physrevb.95.241404
|View full text |Cite
|
Sign up to set email alerts
|

Resistively detected NMR line shapes in a quasi-one-dimensional electron system

Abstract: We observe variation in the resistively-detected nuclear magnetic resonance (RDNMR) lineshapes in quantum Hall breakdown. The breakdown is locally occurred in a gate-defined quantum point contact (QPC) region. Of particular interest is the observation of a dispersive lineshape occured when the bulk 2D electron gas (2DEG) is set to ν b = 2 and the QPC filling factor to the vicinity of νQPC = 1, strikingly resemble the dispersive lineshape observed on a 2D quantum Hall state. This previously unobserved lineshape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The layout and dimensions of the present devices displayed in Fig. 1(a) are similar to those used by Fauzi et al 8 with three independent Schottky gates to define the quantum point contact. Throughout the measurement process, we always equally biased a pair of split gates (V SG ) and set the bias voltage zero to the center gate (V CG ).…”
Section: Pacs Numbersmentioning
confidence: 96%
“…The layout and dimensions of the present devices displayed in Fig. 1(a) are similar to those used by Fauzi et al 8 with three independent Schottky gates to define the quantum point contact. Throughout the measurement process, we always equally biased a pair of split gates (V SG ) and set the bias voltage zero to the center gate (V CG ).…”
Section: Pacs Numbersmentioning
confidence: 96%
“…6b). Such QHE-DL have been seen too [16,53,55], but the opposite shape is perhaps more standard [47].…”
Section: Dispersive Lineshapementioning
confidence: 98%
“…For the latter, we consider the QPC conductance changes upon applying NMR, socalled resistively detected NMR (RD-NMR) [12]. Variations of this setup have been already considered in experiments and theory [3,[13][14][15][16][17], focusing on various phenomena such as conductance hysteresis, nuclear-spin relaxation, the DNSP mechanism, or "dispersive" RD-NMR line shapes. We, however, feel that despite all these investigations, certain general aspects remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of spin-flip scattering as well as spin-conserved scattering in the QH effect breakdown has been manifested by the dynamic nuclear polarization of the host crystal in both integer and fractional regimes [6][7][8][9] . Indeed, resistively detected nuclear magnetic resonance (NMR) [10][11][12] has shown that the electron spin polarization decreases under a high bias in both mesoscopic and macroscopic systems 13 . On the other hand, inter-edge scattering generates shot noise in mesoscopic systems, from which the spin polarization of the transmitted current can be deduced under the assumption that the scattering event is stochastic, i.e., with no correlation 13 .…”
Section: O Imentioning
confidence: 99%